BENTUK PENYAJIAN TARI SELODANG MAYANG DI KERATON AMANTUBILLAH KABUPATEN MEMPAWAH - Saputra, Agus; Tindarika, Regaria; Satrianingsih, Aline Rizky Oktaviari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to describe the form of presentation of Selodang Mayang Dance at the Amantubillah Palace of Mempawah Regency textually and contextually. This research uses a descriptive method with a qualitative form. The approach used in this study is ethnochoreology. A multidisciplinary approach, which seeks to explore the textual and contextual world. The results of this study show that the form of presentation of Selodang Mayang Dance has textual aspects consisting of a variety of movements, accompaniment music, costumes, makeup, performance venues, upper design, floor design, and group composition. then contextually researchers explore the outline of dance history, dance processes, dance development, community characteristics (social), dancer gender, and symbolic in Selodang Mayang Dance. Data collection techniques used in the form of interview techniques, documentation observation and documentation studies. Selodang Mayang Dance is a welcoming dance for important guests who were present at the Robo"™-Robo"™ event at the Amantubillah Palace of Mempawah Regency. The number of dancers in Selodang Mayang Dance is usually an odd number or at least 5 people who are the wrong dancers carry a property called Selodang Mayang